Applied integration model in education plan for learning recovery - Nur Arifah Amran; Puspa Liza Ghazali; Fauzilah Salleh; Nurul Zawani Baharazi (2016)
Islamic insurance, which is known as takaful, has been commonly used by people especially in most Muslim countries ever since it was introduced. The system has raised many new inventions to increase the effectiveness and to satisfy the people’s needs. However, the existing models of takaful do not provide plans for learning disabled children, even though their number is increasing year by year. The learning disabled children can achieve a better condition with consistent guidance hence something must be done to help them. This study discusses the takaful the education plan for learning disabled children, which will contribute a lot to their recovery from learning disability. By applying an integrated model of the takaful education plan, a new recovery model of the takaful education plan is proposed, which consists of a plan that may assist the education of the learning disabled children.